Recurrent ventricular arrhythmias and heart failure induced by osimertinib- a case report - Luo, Jiangying; Zhou, Boda; Yang, Jing; Qian, Hao; Zhao, Yutong; She, Fei; Liu, Fang; Zhang, Ping (Frontiers in Cardiovascular Medicine, 2024)
Background: Osimertinib is a third-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor that has become the first-line treatment for non-small cell lung cancer harboring EGFR mutations, with the potential risk of QT prolongation and heart failure. However, few cases have reported malignant ventricular arrhythmias. Here, we report a case of recurrent ventricular fibrillation (VF) and Torsade de Pointes (TdP) secondary to QT prolongation and heart failure induced by osimertinib. Case summary: A 70-year-old woman presented with chest tightness and dyspnea for 1 week and ventricular fibrillation upon admission, with a medical history of lung adenocarcinoma harboring an EGFR exon 21 p.L858R mutation. She was under osimertinib for 3 months. Electrocardiography after defibrillation suggested QTc prolongation (655 ms) and T wave alternans. Ultrasound cardiography displayed left ventricular ejection fraction (LVEF) of 29% and severe mitral regurgitation. Laboratory tests indicated elevated N-terminal pro-B-type natriuretic peptide and hypokalemia. Genetic testing suggested no pathogenic mutations. We considered acquired long QT syndrome and heart failure with reduced ejection fraction induced by osimertinib as the chief causes of ventricular arrhythmia and hypokalemia as an important trigger. Despite intubation, sedation, and the administration intravenous magnesium and potassium and lidocaine, the patient presented with recurrent TdP, which was managed by a low dose of isoproterenol (ISO, 0.17 ug/min). An implantable cardioverter defibrillator was declined. The patient is surviving without any relapse, with QTc of 490ms and LVEF of 42% after a 6-month follow up. Conclusion: Regular monitoring is required during osimertinib administration, considering the risk of life-threatening cardiac events, such as malignant arrhythmias and heart failure. ISO, with an individual dose and target heart rate, may be beneficial for terminating TdP during poor response to other therapies.